Design and Mechanical Analysis of a Composite T-Type Connection Structure for Marine Structures - Li Xiaowen (Polish Maritime Research, 2020)
A new T-type connection structure consisting of composite sandwich plates, reinforced cores and adhesive was proposed for the construction of lightweight ships to resolve connection problems between bulkheads and decks of composite lightweight ship superstructures. Based on the design principles and mechanical properties of composite structures, the mechanical behaviour of the structure under a dangerous loading condition was investigated. In addition, the ultimate bearing capacities and damage modes were examined, the results of which demonstrated that the strength of the structure is weak, and that the adhesive and reinforced core between the face plate and the web plate is the primary weakness of the structure. A numerical simulation method was verified using the results of the mechanical tests, and five characteristic paths at the connection area were established. The stresses and displacements along the five paths were calculated using the numerical method. Then, variations in the geometric parameter and the strength and weight of the connection were summarised. The optimal angle of the adhesive bonding area is approximately 60°, which supports the optimal design and practical application of the lightweight ship adhesive-bonded connection structure.